Enrobing Ceremony for Municipal Court Judge R. L. "Chip" Putnam in Jury Assembly Room - Watkins, Howard::::::::: (1987)
Judge Putnam speaking at lectern; seated: Judges Steven Vartabedian and Stephen Henry